Pengaruh Penggunaan Kit Remaja Sebagai Media Edukasi Penyuluhan terhadap Sikap Kesiapsiagaan dalam Menghadapi Banjir di SMA Cinta Kasih Tzu Chi Jakarta Barat - FarahKeyllah, Dhewitry Elda; Arinta, Illa (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
Action through disaster risk reduction is very necessary to deal with flood disasters by reducing the threat and vulnerability of those threatened by disaster. Preparedness is one of the stages in anticipating disasters. Knowledge about disasters should be given to the community, especially teenagers, because teenagers are part of society who have an important role in social life. Adolescents have the potential to experience sexual violence, physical-psychological violence and are at risk of being trafficked (human trafficking). Preparedness plays a very important role when facing disasters. The better the attitude towards disasters, the better prepared a person will be to face disasters. This research is included in the type of quantitative research with a quasi-experimental method with a one group pretest-posttest research design. This research was conducted on December 12 2024 at Cinta Kasih Tzu Chi High School, West Jakarta. Class XI female teenagers aged 16-17 years were the respondents in this research. The sampling method used was total sampling with a total of 56 respondents. The results of research using T-test analysis show the influence of knowledge and attitudes on flood preparedness at Cinta Kasih Tzu Chi High School. This is indicated by the p-value (sig) in the T-test being 0.00, where the value is less than 0.05. There is an influence of knowledge and attitudes on flood preparedness at Cinta Kasih Tzu Chi High School, West Jakarta in 2024 with a P-Value < sig (0.05), namely p value = 0.00.